Teaching text comprehension. Content approach and peer interaction in an experimental training - Cardarello, Roberta; Pintus, Andrea (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2019)
Reading literacy is a key competence for lifelong learning, nevertheless it is still critical for Italian students (Mullis, Martin, Foy, Hooper, 2017; INVALSI, 2018). The aim of this quasi-experimental study is identifying effective teaching strategies in order to foster reading comprehension. According to the individualized intervention centered on the reader methodology (Lumbelli, 2009) integrated with a collaborative pairs work activity and class discussion it was designed and carried out a didactic intervention for primary school students in order to stimulate both text integration and inferential skills. The analysis of the data showed a positive effect of the treatment tested, especially in the case of initially less competent students.